Effectiveness of IoT in Water Quality Monitoring and Waste Management towards Environmental Standards Compliance in the West Java Pharmaceutical Industry - Soelistianto, Farida Arinie; Baharuddin, Baharuddin; Muntasir, Muntasir (West Science Interdisciplinary Studies, 2025)
This study investigates the effectiveness of Internet of Things technologies in water quality monitoring and waste management to meet environmental standards in the pharmaceutical industry of West Java, Indonesia. The quantitative approach was used in this study. Data were collected from 55 pharmaceutical companies through a survey using a Likert scale ranging from 1 to 5. Data analysis was done using SPSS version 25. There is a positive correlation between IoT implementation in both water quality monitoring and waste management regarding environmental standards. The firms in which an IoT system was implemented outperformed others in terms of satisfaction of regulatory requirements concerning water quality and waste disposal. It also established the combined effect of IoT in both the domains on overall environmental performance. These findings reflect that IoT technologies have the potential to significantly enhance the contribution of the pharmaceutical industry towards adhering to environmental standards and sustainable development.